The effects of progressive muscular relaxation as a nursing procedure used for those who suffer from stress due to multiple sclerosis - Paolla Gabrielle Nascimento Novais; Karla de Melo Batista; Eliane da Silva Grazziano; Maria Helena Costa Amorim
ABSTRACT Objective: to evaluate the effect of progressive muscle relaxation as a nursing procedure on the levels of stress for sufferers of multiple sclerosis. Method: random clinical trials conducted at the Neurology outpatients unit at a University Hospital. The sample consisted of 40 patients who were being monitored as outpatients (20 in a control group and 20 in an experimental group). The Progressive Muscle Relaxation technique was used. The control variables were collected through interviews that were recorded on forms and on the Perceived Stress Scale that we used. Five meetings were held every fortnight covering a period of eight weeks. The experimental group was advised to carry out daily progressive muscle relaxation activities. After eight weeks of these activities, they were evaluated again to measure their levels of stress. In order to analyze the data used, the software package Statistics for Social Sciences version 19.0 was used. Results: the application of the t test showed a significant reduction in the Perceived Stress Scale scores in the experimental group (p<0.001), which in turn proved that there was a reduction in the levels of stress after the application of the relaxation practic-es. Conclusion: the progressive muscle relaxation activities contributed to the reduction in stress levels for multiple sclerosis suffers and thus can be used in nursing for patients. Clinical Trials Identifier: NCT 02673827.